Design of non-foster circuits realized by transistors and operational amplifiers - Mo, Tao (Nanyang Technological University, 2023)
This report explores the use of a negative impedance converter to create a non-Foster circuit for matching small antennas. This approach overcomes the limitations of passive matching, such as low efficiency and narrow bandwidth, and facilitates wideband and miniaturized antenna design. The study focuses on the properties and applications of non-Foster components, covering the following aspects: